lead-acid batteries
Patent Information
- Application Number
- JP2025058844
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0006】 本開示に係る鉛蓄電池では、良好なIS寿命を確保し得るとともに良好な高温過充電寿命を確保し得る。
Smart Images

Figure 2026166102000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a lead-acid battery. [Background technology]
[0002] Patent Document 1 describes a lead-acid battery comprising a current collector, a positive electrode plate having a positive electrode material supported by the current collector, and a negative electrode plate, wherein the total pore volume per unit mass of the positive electrode material is 0.167 cm³. 3 The value is less than or equal to / g, and the positive electrode material contains fibers, and the average specific surface area of the fibers measured by the BET method using krypton gas as the adsorption gas is 0.25 m². 2 They are proposing a lead-acid battery that is rated at or above / g. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2019-067741 [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] In recent years, the load on lead-acid batteries has been increasing due to the advent of OTA (Over The Air) technology. For example, recent vehicles equipped with idle stop (IS) (or idle stop-start (ISS)) systems are fitted with many electrical components such as drive recorders and electronic mirrors. In IS applications, lead-acid batteries are used in a state of undercharge called a partially charged state (PSOC). When lead-acid batteries are frequently charged and discharged in PSOC, the positive electrode material is prone to softening and detachment, leading to a premature end of life for the lead-acid battery. Adding fibers with a large specific surface area to the positive electrode material improves the lifespan performance (hereinafter also referred to as "IS lifespan") when lead-acid batteries are used as a power source for IS vehicles (see Patent Document 1). On the other hand, there is room for improvement in lifespan performance when subjected to repeated high-temperature overcharging (hereinafter also referred to as "high-temperature overcharge lifespan"). [Means for solving the problem]
[0005] One aspect of the present invention relates to a lead-acid battery comprising a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate includes a positive electrode material, the positive electrode material includes fibers, and the average surface roughness Ra of the fibers is 0.1 μm or more and 1.3 μm or less. [Effects of the Invention]
[0006] The lead-acid battery relating to this disclosure can ensure a good IS lifespan and a good high-temperature overcharge lifespan. [Brief explanation of the drawing]
[0007] [Figure 1] This is a partially cutaway perspective view showing the external appearance and internal structure of a lead-acid battery according to one embodiment of the present disclosure. [Figure 2] This is a SEM image showing the appearance of an example of polyester fiber. [Figure 3] This is a SEM image showing the appearance of an example of acrylic fiber. [Modes for carrying out the invention]
[0008] The embodiments of this disclosure will be described below with examples, but this disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be given as examples, but other numerical values and materials may be applied as long as the effects of this disclosure are obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "greater than or equal to numerical value A and less than or equal to numerical value B". In the following description, when lower and upper limits of numerical values relating to specific physical properties or conditions are given as examples, either of the given lower limits and either of the given upper limits can be arbitrarily combined, as long as the lower limit is not greater than or equal to the upper limit. When multiple materials are given as examples, one of them may be selected and used alone, or two or more may be used in combination.
[0009] Furthermore, the present disclosure encompasses combinations of the matters described in two or more claims arbitrarily selected from a plurality of claims described in the appended claims. That is, as long as no technical contradiction arises, the matters described in two or more claims arbitrarily selected from the plurality of claims described in the appended claims can be combined with each other.
[0010] The lead-acid battery according to the present disclosure may be a flooded battery (vented type battery) or a valve-regulated battery (VRLA battery). Lead-acid batteries for IS vehicles tend to be required to be lightweight from the viewpoint of improving fuel efficiency. Flooded lead-acid batteries are suitable for IS vehicles in that they are lighter than VRLA batteries.
[0011] A lead-acid battery includes a positive electrode plate, a negative electrode plate, a separator interposed between the positive electrode plate and the negative electrode plate, and an electrolytic solution. The electrolytic solution contains sulfuric acid. Charging and discharging proceed as sulfate ions move between the positive and negative electrode plates and the electrolytic solution. During discharging, sulfate ions move to the positive electrode plate and the negative electrode plate. During charging, sulfate ions move from the positive electrode plate and the negative electrode plate into the electrolytic solution.
[0012] The positive electrode plate, the negative electrode plate, and the separator constitute an electrode plate group. The electrode plate group constitutes a cell together with the electrolytic solution. One electrode plate group constitutes one cell. A lead-acid battery is provided with one or more cells by being equipped with one or more electrode plate groups. The number of positive electrode plates and negative electrode plates included in one electrode plate group is not particularly limited. The electrode plate group included in the lead-acid battery according to the present disclosure includes, for example, 12 or more positive and negative electrode plates in total. The plurality of electrode plate groups are usually each housed in individual cell chambers and connected in series to each other.
[0013] The positive electrode plate contains a positive electrode material. The positive electrode material contains at least lead dioxide during charging and at least lead sulfate during discharging as a positive electrode active material that develops capacity through an oxidation-reduction reaction.
[0014] The negative electrode plate contains a negative electrode material. The negative electrode material contains at least lead during charging and at least lead sulfate during discharging as a negative electrode active material that develops capacity through an oxidation-reduction reaction.
[0015] (1) A lead-acid battery according to one embodiment of the present disclosure comprises a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate includes a positive electrode material, the positive electrode material includes fibers, and the average surface roughness Ra of the fibers is 0.1 μm or more and 1.3 μm or less. The fibers function as a reinforcing material for the positive electrode material.
[0016] In the lead-acid battery described in (1) above, the average surface roughness Ra of the fibers contained in the positive electrode material is 0.1 μm or more, so the surface of the fibers has a moderate roughness. Fibers with a larger average roughness Ra can exhibit a higher anchoring effect, making it less likely for the positive electrode material to detach from the positive electrode plate, thus ensuring a good IS life. On the other hand, when the average surface roughness Ra of the fibers is 1.3 μm or less, the surface of the fibers does not have excessive irregularities. Therefore, even when high-temperature overcharging is repeated, oxidative degradation of the fiber surface is less likely to progress. As a result, a state of high adhesion between the fibers and the positive electrode material is maintained for a long period of time, and a good high-temperature overcharging life can also be ensured.
[0017] When the average surface roughness Ra of a fiber exceeds 1.3 μm, and the fiber surface has excessive irregularities, the positive electrode material easily penetrates the depressions on the fiber surface, and the convex parts of the fiber surface easily penetrate the gaps in the positive electrode material. As a result, the adhesion between the fiber and the positive electrode material increases. Since the positive electrode material is a strong oxidizing agent, if the adhesion between the fiber and the positive electrode material is too high, repeated high-temperature overcharging can easily lead to oxidative degradation of the fiber starting from the irregularities. More specifically, oxidative degradation mainly progresses on the convex parts of the fiber, making the fiber brittle and prone to breakage starting from the convex parts. This reduces the adhesion between the fiber and the positive electrode material, making it difficult to prevent the detachment of the positive electrode material.
[0018] Conventionally, it has been believed that the larger the specific surface area of the fibers, the more effectively the softening and shedding of the positive electrode material can be suppressed. However, simply increasing the specific surface area of the fibers has limitations in its effectiveness in suppressing the softening and shedding of the positive electrode material. This is because even if the specific surface area of the fibers is increased by creating irregularities on the fiber surface that are prone to oxidative degradation, the fibers are still oxidized by the positive electrode material, mainly during high-temperature overcharging. To suppress such oxidative degradation of fibers, it is necessary to control the average surface roughness Ra of the fibers.
[0019] When the average surface roughness Ra of the fibers is controlled to be between 0.1 μm and 1.3 μm, the fibers can have a sufficient anchoring effect and ensure good oxidation resistance. Therefore, it becomes possible to obtain lead-acid batteries with excellent IS life and high-temperature overcharge life.
[0020] The high-temperature overcharge lifespan of lead-acid batteries can be evaluated in the "High-Temperature Overcharge Lifespan Test" described below.
[0021] (2) In the lead-acid battery described in (1) above, the BET specific surface area measured using krypton gas as the adsorbent gas is 0.3 m². 2 / g or more 1.0m 2 It is preferable that the value be less than or equal to / g.
[0022] In the lead-acid battery described in (2) above, the BET specific surface area measured using krypton gas from the fibers contained in the positive electrode material as the adsorbent gas is 0.3 m². 2 Because the fiber density is moderately large, at or above / g, a sufficient contact area with the positive electrode material can be secured, resulting in a high effectiveness in suppressing the shedding of the positive electrode material. Furthermore, when the average surface roughness Ra of the fiber is between 0.1 μm and 1.3 μm, the fiber surface tends to be smooth, the number of protrusions that can form on the fiber surface is small, and oxidative degradation by the positive electrode material is less likely to progress. In such fibers, a good balance between the anchoring effect and oxidation resistance of the fiber is ensured, as a sufficient contact area with the positive electrode material is secured while oxidative degradation by the positive electrode material is less likely to progress.
[0023] Furthermore, the BET specific surface area of the fiber measured using krypton gas as the adsorption gas was 1.0 m². 2 When the value is less than / g, contact between the fibers and the positive electrode material is moderately suppressed, so the insulating fibers are less likely to interrupt the conductive path. Therefore, the conductive path of the positive electrode material is easily secured. Thus, the positive electrode plate can ensure good conductivity, and it becomes possible to obtain a lead-acid battery with superior IS life.
[0024] As described above, the BET specific surface area of the fiber measured using krypton gas as the adsorption gas is 0.3 m². 2 / g or more 1.0m 2 By controlling the load to less than / g, it becomes possible to obtain a lead-acid battery with superior performance in both IS lifespan and high-temperature overcharge lifespan.
[0025] (3) In the lead-acid battery described in (1) or (2) above, the fiber content in the positive electrode material may be 0.05% by mass or more and 0.23% by mass or less.
[0026] In the lead-acid battery described in (3) above, the effect of the fibers is fully realized, making it possible to obtain a lead-acid battery with even better IS life and high-temperature overcharge life. Furthermore, because the fiber content in the positive electrode material is appropriate, the insulating fibers are less likely to disrupt the conductive path. Therefore, the conductive path of the positive electrode material is easily secured. Thus, the positive electrode plate can ensure good conductivity, making it possible to obtain a lead-acid battery with superior IS life.
[0027] (Method for measuring the average surface roughness Ra of fibers) The average surface roughness Ra of a fiber is determined by the following procedure. For measurement, fibers taken from the positive electrode material of a fully charged lead-acid battery are used.
[0028] The positive electrode material is recovered from the positive electrode plate by the following procedure. First, a fully charged lead-acid battery is disassembled, and the electrolyte in the positive electrode plate is removed by washing it with water for 3 to 4 hours. The washed positive electrode plate is dried in a constant temperature bath at 60°C ± 5°C for 5 hours or more. A bonding material containing fibers, such as a mat, and / or a nonwoven fabric separator may be attached to the positive electrode plate. The fibers contained in the bonding material and nonwoven fabric are not included in the fibers of the present invention. If a bonding material and / or nonwoven fabric was attached to the positive electrode plate, the surface of the positive electrode plate is scraped off until the residue of the bonding material and / or nonwoven fabric is removed, in order to prevent fibers derived from the bonding material and / or nonwoven fabric from mixing into the positive electrode material, before the positive electrode material is collected. For example, the residue may be evenly scraped off from the surface layers on both sides of the positive electrode plate before the positive electrode material is collected. At this time, it is desirable to scrape off a depth of approximately 0.03 mm to 0.20 mm on each side. Then, by taking a sample of the positive electrode material for analysis from near the center when viewing the positive electrode plate from the front, without crushing it, a sample of the positive electrode material can be obtained.
[0029] The fibers are recovered from the positive electrode material sample by the following procedure. First, the positive electrode material sample is crushed. At this time, the positive electrode material contained in one or more positive electrode plates may be used as the sample.
[0030] Next, the pulverized sample is added to a mixed solution of acetic acid-sodium acetate solution and sodium thiosulfate solution (acetic acid concentration 1.7 mol / L, sodium acetate concentration 6.1 mol / L, sodium thiosulfate concentration 0.5 mol / L), and the soluble components are dissolved while stirring at room temperature. Then, the resulting residue is filtered using a membrane filter (average pore size: 0.45 μm or less). During filtration, the residue (fibers) is washed with deionized water. This allows the fibers contained in the positive electrode material to be obtained as solid matter on the filter paper.
[0031] A fiber sample for analysis is obtained by washing and drying the resulting solid material. The average surface roughness Ra of the fiber is determined using a laser microscope in accordance with ISO 4287:1997. Specifically, an image for analysis is acquired with a 20x objective lens. The acquired image for analysis is subjected to automatic correction processing for noise reduction and tilt correction using an analysis application. An image for analysis is acquired from five or more fibers, and the line roughness measurement is performed using the analysis application to analyze each fiber. The surface roughness Ra of each fiber is measured, and the average surface roughness Ra of the five or more measured values is determined. The analysis is performed with all filter conditions (F calculation, S filter, L filter) set to none.
[0032] The following can be used as measuring devices: Laser microscope: VK-X3000, manufactured by Keyence Corporation. Objective lens: Nikon Corporation, Plan x20 NA 0.46 WD 3.1mm Analysis application: VK-A3, manufactured by Keyence Corporation.
[0033] (Measurement of BET specific surface area) The BET specific surface area of fibers measured using krypton gas as the adsorption gas is determined for fibers taken from the positive electrode material of a fully charged lead-acid battery. For the fiber samples for analysis obtained by the procedure described above, the BET specific surface area is determined using krypton gas as the adsorption gas, in accordance with the calculation method for BET specific surface area in JIS Z 8830:2013, 7.2.
[0034] The following can be used as measuring devices. Preferred measuring conditions are also shown below. Measuring device: Shimadzu Corporation, TriStar II 3020 series Adsorption gas: Krypton gas with a purity of 99.99% or higher. Adsorption temperature: -196℃
[0035] (Measurement of fiber content) The fiber content in the positive electrode material is determined for fibers collected from the positive electrode material of a lead-acid battery in a fully charged state. First, the mass W (g) of the positive electrode material recovered by the procedure described above is measured in advance. Subsequently, the mass w (g) of the fiber sample for analysis obtained from the positive electrode material of mass W (g) by the procedure described above is measured. The ratio (percentage) of the mass w of the fiber sample to the mass W of the positive electrode material sample is the fiber content in the positive electrode material.
[0036] <Fully charged state> In the present specification, the fully charged state of a flooded lead-acid battery is defined by the definition of JIS D5301:2019. More specifically, in a water tank at 25°C ± 2°C, the terminal voltage during charging (unit: V) measured every 15 minutes or the electrolyte density temperature-converted to 20°C is kept constant to 3 significant digits for 3 consecutive times, at the 20-hour rate current I 20 a current of 2 times 2I 20 (unit: A), the state where the lead-acid battery is charged is defined as the fully charged state. The 20-hour rate current I 20 refers to a current (A) that is 1 / 20 of the Ah value described in the rated capacity. The value described as the rated capacity is a value with the unit Ah (ampere-hour). The unit of the current set based on the value described as the rated capacity is A (ampere).
[0037] Further, in the case of a valve-regulated lead-acid battery, the fully charged state means that in an air tank at 25°C ± 2°C, at the 20-hour rate current I 20 a current of 5 times 5I 20 constant current constant voltage charging is performed at 2.67 V / cell (16.00 V for a lead-acid battery with a nominal voltage of 12 V), and the charging is terminated when the total charging time reaches 24 hours.
[0038] A lead-acid battery in a fully charged state is a lead-acid battery obtained by charging a formed lead-acid battery to a fully charged state. The timing for charging the lead-acid battery to the fully charged state may be immediately after formation as long as it is after formation, or may be after a period of time (for example, 720 hours or less) has elapsed since formation. For example, the lead-acid battery in use (preferably in the initial stage of use) after formation may be charged.
[0039] In this specification, a battery in its initial use refers to a battery that has not been used for very long and has not deteriorated much (for example, a battery that has been in use for less than 720 hours, including the time elapsed since chemical preparation).
[0040] The lead-acid battery according to an embodiment of the present invention will be described in more detail below with reference to the drawings. However, the present invention is not limited to the following embodiments.
[0041] The following describes examples of components of a lead-acid battery.
[0042] (Positive plate) The positive electrode plate comprises a positive electrode current collector and a positive electrode material. The positive electrode material is held by the positive electrode current collector. The positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector. Adhesive members such as conductive layers, mats, and pasting paper may be attached to the positive electrode plate. Since the adhesive members are used integrally with the positive electrode plate, they are included as components of the positive electrode plate. When the positive electrode plate includes adhesive members, the positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector and the adhesive members.
[0043] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or by processing a lead or lead alloy sheet. Processing methods may include, for example, expansion or punching. Using a grid-like current collector as the positive electrode current collector makes it easier to support the positive electrode material.
[0044] As the lead alloy used for the positive electrode current collector, Pb-Ca alloys and Pb-Ca-Sn alloys, which have excellent corrosion resistance and mechanical strength, are preferred. The positive electrode current collector may have metal layers of different compositions, and the metal layers may be one layer or multiple layers.
[0045] The positive electrode material includes a positive electrode active material that exhibits capacity through a redox reaction. The positive electrode active material includes lead dioxide, lead sulfate, etc. The positive electrode material also includes fibers as a reinforcing material and may include antimony compounds, etc., as needed.
[0046] The average surface roughness Ra of the fibers is 0.1 μm or more and 1.3 μm or less, preferably 0.2 μm or more and 1 μm or less, and more preferably 0.3 μm or more and 0.7 μm or less. If the average surface roughness Ra of the fibers is less than 0.1 μm, the contact area between the fibers and the positive electrode material becomes excessively small, and the anchoring effect by the fibers is not sufficiently realized. As a result, softening of the positive electrode material and detachment of the positive electrode material from the positive electrode current collector cannot be suppressed, and good IS life performance cannot be ensured. Furthermore, if the average surface roughness Ra of the fibers exceeds 1.3 μm, excessive irregularities that are prone to oxidative degradation are formed on the surface of the fibers, and oxidative degradation of the fibers by the positive electrode material cannot be suppressed, and good high-temperature overcharge life cannot be ensured.
[0047] The average surface roughness Ra of the fibers may be adjusted in advance by surface treatment of the fibers, or the average surface roughness Ra of fibers whose surface roughness Ra has not been adjusted may be adjusted by a predetermined method, or it may be adjusted during the manufacturing process of the lead-acid battery. One method for adjusting the average surface roughness Ra of the fibers is chemical treatment, which modifies the fiber surface using chemicals such as acids and alkalis. Other methods for adjusting the average surface roughness Ra of the fibers include plasma treatment, which modifies the fiber surface using plasma, corona treatment, which modifies the fiber surface using high-voltage discharge, and UV irradiation treatment, which modifies the fiber surface using ultraviolet light. Another method is sandblasting, for example. Sandblasting is a process in which fine powder harder than the fibers is impacted onto the fibers.
[0048] For example, when performing plasma treatment, corona treatment, or UV irradiation as a method for treating the surface of fibers, the average surface roughness Ra of the fibers may be adjusted by changing the output value of the processing device, the processing time, or both. In sandblasting, the speed of the fine powder impacting the fibers and the processing time can also be changed.
[0049] The fiber has a BET specific surface area measured using krypton gas as the adsorbent gas, for example, 0.3 m².2 / g or more 1.0m 2 It may be less than or equal to / g, and more preferably 0.4m 2 / g or more 0.6m 2 It may be less than / g. The BET specific surface area of the fiber measured using krypton gas as the adsorbent gas is 0.3m². 2 When the value is 1 / g or higher, the contact area between the fiber and the positive electrode material becomes sufficiently large, making it easier to ensure even better IS lifetime performance. In addition, the BET specific surface area of the fiber measured using krypton gas as the adsorption gas is 1.0 m². 2 When the value is less than / g, the oxidation resistance of the fibers is further improved, and the positive electrode plate can more easily ensure sufficient conductivity.
[0050] The BET specific surface area of a fiber may be adjusted, for example, by surface treatment of the fiber, similar to the adjustment of the average surface roughness Ra of the fiber. Alternatively, the average surface roughness Ra and the BET specific surface area of the fiber may be adjusted simultaneously by surface treatment of the fiber. Methods for treating the fiber surface include those described above, such as chemical treatment, plasma treatment, corona treatment, UV irradiation treatment, and sandblasting. It may also be adjusted by controlling the average fiber diameter.
[0051] The fiber content in the positive electrode material may be, for example, 0.05% by mass or more and 0.23% by mass or less, and more preferably 0.04% by mass or more and 0.14% by mass or less. When the fiber content in the positive electrode material is 0.05% by mass or more, the effect of the fibers is fully realized, and even better IS lifetime performance can be ensured. Also, when the fiber content in the positive electrode material is 0.23% by mass or less, the fiber content in the positive electrode material is appropriate, so the insulating fibers are less likely to interrupt the conductive path. As a result, the conductivity of the positive electrode plate becomes even better.
[0052] The resin constituting the fiber may be, for example, polyester, polyolefin, polystyrene, polyvinyl chloride, polyurethane, acrylic resin, vinylon, etc. Among these, at least one selected from the group consisting of polyester, polystyrene, and polyurethane is preferred. Examples of polyester include polyalkylene arylates such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). Examples of polyolefins include polyethylene, polypropylene, and ethylene-propylene copolymer. The fiber may contain one of these resins or two or more. Furthermore, the positive electrode material may contain multiple fibers formed of different resins. In particular, using PET makes it easier to improve the IS lifespan performance of lead-acid batteries. PET has excellent acid resistance and mechanical strength. Therefore, fibers composed of PET have a fine average fiber diameter and can secure a large surface area even in small quantities, which has a great effect on improving the IS lifespan performance of lead-acid batteries. In addition, PET fibers are inexpensive.
[0053] For example, 85% or more by mass of the fiber may be at least one selected from the group consisting of polyester, polystyrene, polyurethane, and polyolefin. Fibers containing polyester, polystyrene, polyurethane, or polyolefin in such a high mass content are usually referred to as polyester fibers, polystyrene fibers, polyurethane fibers, or polyolefin fibers.
[0054] The type of resin constituting the fibers contained in the positive electrode material can be identified by analyzing the fibers recovered from the positive electrode material using the method described above, according to the method described in JIS L 1030-1:2024.
[0055] The resin constituting the fibers can be identified by analyzing the infrared absorption spectrum of the fiber sample. Method B (film method) specified in JIS L 1030-1:2024 may be used as the analytical method.
[0056] Specifically, the fiber sample is dissolved in an appropriate dissolving reagent (see Table A), poured into an evaporating dish, and dried under vacuum or by heating to a temperature that does not decompose the sample. Next, the dried film is peeled off without tearing, cut to an appropriate size, and the infrared absorption spectrum is measured in accordance with JIS K 0117:2017. The film should be of a thickness that makes it transparent. Also, the size of the film will vary depending on the infrared spectrophotometer used, so it should be at least 1 cm. 2 That concludes this section.
[0057] Table A exemplifies the main absorption bands and characteristic wavenumbers of the infrared absorption spectra of major fibers, as well as the dissolving reagents. The absorption bands and characteristic wavenumbers of each fiber vary by ±20 cm depending on the infrared spectrophotometer used. -1 There are differences in degree.
[0058] [Table A]
[0059] Unformed positive electrode plates are obtained by maturing and drying a positive electrode current collector and a positive electrode paste filled in the positive electrode current collector. The positive electrode paste is prepared by kneading a mixture containing lead powder, fibers, water, and sulfuric acid. The positive electrode paste may contain additives as needed. These additives may include antimony compounds, for example. Such positive electrode plates are also called paste-type positive electrode plates.
[0060] A positive electrode plate can be obtained by chemically treating an untreated positive electrode plate. Chemical treatment may be carried out by immersing the electrode plate group, including the untreated positive electrode plate, in an electrolyte containing sulfuric acid in the battery case of a lead-acid battery, and charging the electrode plate group. Chemical treatment may also be carried out before the assembly of the lead-acid battery or the electrode plate group.
[0061] (Negative electrode plate) The negative electrode plate comprises a negative electrode current collector and a negative electrode material. The negative electrode material is held by the negative electrode current collector. The negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector. Note that adhesive members such as conductive layers, mats, and pasting paper may be attached to the negative electrode plate. The adhesive members are included as components of the negative electrode plate. When the negative electrode plate includes adhesive members, the negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector and the adhesive members.
[0062] The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or by processing a lead or lead alloy sheet. The processing method may be expansion or punching. Using a grid-like current collector as the negative electrode current collector makes it easier to support the negative electrode material.
[0063] The lead alloy used for the negative electrode current collector may be any of the following: a Pb-Sb alloy, a Pb-Ca alloy, or a Pb-Ca-Sn alloy. The lead alloy used for the negative electrode current collector may also contain at least one additive element selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. The negative electrode current collector may have metal layers of different compositions, and the metal layers may be one layer or multiple layers.
[0064] The negative electrode material contains a negative electrode active material that exhibits capacity through a redox reaction. The negative electrode active material includes lead, lead sulfate, etc. The negative electrode material may also contain Bi element in an amount of 100 ppm to 300 ppm by mass. The negative electrode material may contain other additives as needed. The additives may include organic shrinkage inhibitors, carbonaceous materials, barium sulfate, etc.
[0065] Examples of organic shrinkage inhibitors include lignin, lignin sulfonic acid, and synthetic organic shrinkage inhibitors. Synthetic organic shrinkage inhibitors may be, for example, formaldehyde condensates of phenolic compounds. Organic shrinkage inhibitors may be used individually or in combination of two or more. The content of organic shrinkage inhibitors in the negative electrode material is, for example, 0.01% by mass or more and 1% by mass or less.
[0066] As carbonaceous materials, carbon black, artificial graphite, natural graphite, hard carbon, soft carbon, etc., can be used. One type of carbonaceous material may be used alone, or two or more types may be used in combination. The carbonaceous material content in the negative electrode material is, for example, 0.1% by mass or more and 3% by mass or less.
[0067] The barium sulfate content in the negative electrode material is, for example, 0.1% by mass or more and 3% by mass or less.
[0068] Unformed negative electrode plates are obtained by aging and drying a negative electrode current collector and a negative electrode paste filled in the negative electrode current collector. Aging is preferably carried out in an atmosphere with a temperature higher than room temperature and high humidity. The negative electrode paste is prepared by kneading a mixture containing lead powder, water, and sulfuric acid. The negative electrode paste may contain additives as needed. Additives may include bismuth compounds (e.g., bismuth sulfate), organic shrinkage inhibitors, carbonaceous materials, barium sulfate, etc.
[0069] A negative electrode plate can be obtained by chemically treating an untreated negative electrode plate. Chemical treatment may be carried out by immersing a group of electrode plates, including the untreated negative electrode plate, in an electrolyte containing sulfuric acid in the battery case of a lead-acid battery, and charging the electrode plate group. Chemical treatment may also be carried out before the assembly of the lead-acid battery or the electrode plate group. The charged negative electrode active material contains spongy lead.
[0070] (Separator) Lead-acid batteries typically have a separator between the negative and positive electrodes. The separator may be a microporous membrane or an absorbed glass mat (AGM).
[0071] A microporous membrane is a porous sheet mainly composed of materials other than fiber components. Preferably, the amount of materials other than fiber components is, for example, 60% by mass or more. A microporous membrane can be obtained, for example, by extruding a resin composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. A microporous membrane is preferably composed of an acid-resistant polymer component. Polyolefin is preferred as the polymer component. On the other hand, a glass fiber mat preferably contains, for example, 60% by mass or more glass fibers.
[0072] The thickness of the separator placed between the negative electrode plate and the positive electrode plate should be selected according to the distance between the two plates.
[0073] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may be gelled as needed. The electrolyte may optionally contain cations (e.g., metal cations) and / or anions (e.g., phosphate ions) not derived from sulfuric acid. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0074] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is, for example, 1.20 or higher, and may be 1.25 or higher. The specific gravity of the electrolyte at 20°C is 1.35 or lower, and preferably 1.32 or lower.
[0075] (Example of a lead-acid battery) Figure 1 shows the external appearance and part of the internal structure of a lead-acid battery according to one embodiment. The lead-acid battery 1 comprises a battery case 12 that houses an electrode plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a number of cell chambers 14 by a partition wall 13. Each cell chamber 14 houses one electrode plate group 11. The opening of the battery case 12 is closed with a lid 15 equipped with a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When replenishing water, the vent plug 18 is removed and the water is replenished. The vent plug 18 may also have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0076] Each electrode plate group 11 is constructed by stacking multiple negative electrode plates 2 and positive electrode plates 3 via separators 4. Here, a bag-shaped separator 4 that houses the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In the cell chamber 14 located at one end of the battery case 12, a negative electrode strap 6 connecting multiple negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode strap 5 connecting multiple positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 on the outside of the lid 15. In the cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode strap 6, and a through connector 8 is connected to the positive electrode strap 5. The negative electrode column 9 is connected to a negative electrode terminal 16 on the outside of the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13, connecting the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0077] Note that Figure 1 is merely one example of a liquid-type lead-acid battery, and the structure of the lead-acid battery relating to this disclosure is not limited to the example shown.
[0078] [Examples] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0079] The evaluation methods for fibers and lead-acid batteries are described below. For the evaluation of lead-acid batteries, a lead-acid battery (nominal voltage 12V) is used, which consists of six cells (connected in series) with four JIS B size positive electrodes and five JIS B size negative electrodes. The evaluation method is described below.
[0080] (IS Life Test Method) In this specification, the IS life of a lead-acid battery is evaluated by the number of charge-discharge cycles in the IS life test (SBA S 0101:2014).
[0081] For a fully charged lead-acid battery with a nominal voltage of 12V, the procedure can be carried out according to (a) and (b) below. (a) Throughout the entire test period, the lead-acid battery shall be placed in a gas phase at 25±2℃. The wind speed near the lead-acid battery shall be 2.0 m / s or less. (b) Connect the lead-acid battery to the life test device and perform the following discharge (discharge 1 and discharge 2) and charge. This discharge and charge constitutes one cycle of discharge and charge. Then, repeat the discharge and charge cycle continuously. Discharge 1: Discharge current I D 59.0 ± 0.2 seconds at ±1A (where, I D This is calculated using the following conversion formula and rounded to the first decimal place. D = 18.3 × I 20 ) Discharge 2: Discharge current 300±1A for 1.0±0.2 seconds Charging: Charging voltage 14.00±0.03V (limiting current 100.0±0.5A) for 60.0±0.3 seconds After every 3600 cycles, leave the system for 40-48 hours before starting the cycle again. Do not add water until the 30,000th cycle. The discharge termination voltage (terminal voltage) of discharge 2 is measured, and the number of cycles until it reaches 7.2V is determined and used as an indicator of IS life.
[0082] (High-temperature overcharge life test method) In this specification, the high-temperature overcharge life of a lead-acid battery is evaluated by the number of charge-discharge cycles in the high-temperature overcharge life test according to the procedure described below.
[0083] For a fully charged lead-acid battery with a nominal voltage of 12V, the procedure can be carried out according to the steps (a) to (d) below. (a) Throughout the entire test period, the lead-acid battery will be placed in the gas phase at 75±3℃. (b) Connect the lead-acid battery to the life test device and continuously repeat the following discharge and charge cycles. Each of these discharge and charge cycles constitutes one life cycle. Discharge: Discharge current 25.0A ± 0.1A for 60 seconds ± 1 second Charging: Charging voltage 14.80V ± 0.03V (limiting current 25.0A ± 0.1A) for 600 seconds ± 1 second (c) During testing, leave the device idle for 56 hours every 480 cycles, and then run the rated cold cranking current I cc Perform a continuous discharge for 30 seconds and record the voltage at the 30-second mark. Then, perform the charging procedure described in (b). Note that these discharge and charge cycles will also be added to the lifespan (number of cycles). The test is terminated when the voltage measured at 30 seconds in test (d)(c) is 7.2V or less and does not rise again, and the total number of cycles at this time is used as an indicator of high-temperature overcharge life. Note that the rated cold cranking current I cc This refers to the current value corresponding to the performance rank specified in JIS D 5301:2019.
[0084] Lead-acid batteries E1-E18 and R1-R3 (1) Fabrication of the negative electrode plate A negative electrode paste was prepared by mixing lead oxide, carbon black, barium sulfate, lignin, water, and sulfuric acid. The negative electrode paste was filled into the mesh of an expanded grid made of antimony-free Pb-Ca-Sn alloy, and then aged and dried to obtain an unformed negative electrode plate of JIS B size. The amounts of carbon black, barium sulfate, and lignin were adjusted so that they were 0.3 mass%, 2.1 mass%, and 0.1 mass%, respectively, when measured in a fully charged, pre-formed state.
[0085] (2) Fabrication of the positive electrode plate A positive electrode paste was prepared by mixing lead oxide, fibers, water, and sulfuric acid. At this time, the surface irregularities of the fibers were adjusted by one of the methods described above so that the average surface roughness Ra of the fibers, determined by the method described above, and the BET specific surface area of the fibers, determined using krypton gas as the adsorbent gas, were the values shown in Table 1. In addition, the fibers were added to the positive electrode paste so that the fiber content in the positive electrode material, determined by the method described above, was the value shown in Table 1. The positive electrode paste was filled into the mesh of an expanded grid made of antimony-free Pb-Ca-Sn alloy, aged, and dried to obtain an unformed positive electrode plate of JIS B size.
[0086] The resins that make up the fibers used are as follows: PET: Polyethylene terephthalate Vinylon: A synthetic fiber obtained by acetalizing polyvinyl alcohol. Acrylic: Acrylic resin PS: Polystyrene PU: Polyurethane PE: Polyethylene
[0087] Figure 2 shows an SEM image of a PET fiber with a surface textured surface. Figure 3 shows an SEM image of an acrylic fiber with a surface textured surface. To suppress charge-up during SEM imaging, a conductive material (gold or carbon) may be deposited onto the fiber surface before imaging.
[0088] (3) Fabrication of separators A bag-shaped separator was prepared by folding a polyethylene microporous membrane in half.
[0089] (4) Manufacturing of lead-acid batteries Each untreated negative electrode plate was placed in a bag-shaped separator, and five untreated negative electrode plates and four untreated positive electrode plates were stacked alternately to form an electrode plate group. The tabs of the positive electrode plates and the tabs of the negative electrode plates were welded to the positive and negative electrode straps, respectively, using the cast-on-strap (COS) method. The electrode plate group was inserted into a polypropylene battery case, electrolyte was poured in, and the electrode plate group was treated within the case to assemble a liquid-type lead-acid battery with a nominal voltage of 12V and a rated capacity of 30Ah (20-hour rate capacity). Six electrode plate groups are connected in series within the battery case.
[0090] The density of the electrolyte after chemical conversion is 1.12–1.26 g / cm³. 3 It was adjusted within that range.
[0091] (5) Evaluation The fabricated lead-acid batteries were fully charged using the procedure described above, and their IS life (number of cycles until the terminal voltage of the lead-acid battery falls below 7.2V) and high-temperature overcharge life (number of cycles until the voltage at 30 seconds falls below 7.2V) were determined. The results are shown in Table 1. Each evaluation is expressed as a relative value (%) with the result of lead-acid battery R2 set to 100%.
[0092] [Table 1]
[0093] 《Lead acid battery R4~R7》 Except for adjusting the surface irregularities of the fibers by surface treatment so that the average surface roughness Ra of the fibers, obtained by the method described above, and the BET specific surface area of the fibers, obtained using krypton gas as the adsorbent gas, were the values shown in Table 2, batteries R4 to R7 were fabricated and evaluated in the same manner as battery E3. The results are shown in Table 2.
[0094] [Table 2]
[0095] 《Lead acid battery R8~R11》 Batteries R8 to R11 were prepared in the same manner as battery R1, except that the fibers were incorporated into the positive electrode paste so that the fiber content in the positive electrode material, as determined by the method described above, was as shown in Table 3, and were evaluated in the same manner. The results are shown in Table 3.
[0096] [Table 3]
[0097] From the results for batteries E1 to E18 in Table 1, it can be seen that when the average surface roughness Ra of the fibers is between 0.1 μm and 1.3 μm, a good IS life and a good high-temperature overcharge life can be ensured. It is thought that fibers with a higher average surface roughness Ra can exhibit a higher anchoring effect, making it less likely for the positive electrode material to detach from the positive electrode plate, thus ensuring a good IS life. Furthermore, when the average surface roughness Ra of the fibers is 1.3 μm or less, oxidative degradation of the fibers is less likely to progress even when high-temperature overcharging is repeated, and the fibers can remain in the positive electrode material for a longer period. As a result, it is thought that a state of high adhesion between the fibers and the positive electrode material is maintained for a long period, and a good high-temperature overcharge life can be ensured.
[0098] On the other hand, the results for battery R1 in Table 1 show that if the average surface roughness Ra of the fibers is less than 0.1 μm, a good IS life cannot be ensured. Furthermore, the results for batteries R2 and R3 in Table 1 show that if the average surface roughness Ra of the fibers exceeds 1.3 μm, a good high-temperature overcharge life cannot be ensured.
[0099] From the results for batteries E3, E13, and E18 in Table 2, the BET specific surface area of the fiber measured using krypton gas as the adsorption gas is 0.3 m². 2 / g or more 1.0m 2 When the value is less than / g, it can be seen that an even better IS lifespan and an even better high-temperature overcharge lifespan can be ensured.
[0100] From the results for batteries E3, E6, and E12 in Table 3, it can be seen that when the fiber content in the positive electrode material is between 0.05% by mass and 0.23% by mass, an even better IS life and an even better high-temperature overcharge life can be ensured. [Industrial applicability]
[0101] The lead-acid battery according to the above aspects of the present invention is suitable, for example, for IS (idle stop) applications (such as lead-acid batteries for ISS (idle stop start) vehicles), and as a starting power source for various vehicles (automobiles, motorcycles, etc.). However, these applications are merely examples, and the lead-acid battery according to the above aspects of the present invention is not limited to these applications. [Explanation of symbols]
[0102] 1: Lead-acid battery, 2: Negative electrode plate, 3: Positive electrode plate, 4: Separator, 5: Positive electrode strap, 6: Negative electrode strap, 7: Positive electrode post, 8: Through connector, 9: Negative electrode post, 11: Electrode plate group, 12: Battery case, 13: Partition wall, 14: Cell chamber, 15: Cover, 16: Negative electrode terminal, 17: Positive electrode terminal, 18: Electrode cap
Claims
1. It comprises a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode material, The positive electrode material includes fibers, A lead-acid battery in which the average surface roughness Ra of the aforementioned fibers is 0.1 μm or more and 1.3 μm or less.
2. The aforementioned fiber has a BET specific surface area of 0.3 m², measured using krypton gas as the adsorbent gas. 2 / g or more 1.0m 2 The lead-acid battery according to claim 1, wherein the value is less than or equal to / g.
3. The lead-acid battery according to claim 1, wherein the fiber content in the positive electrode material is 0.05% by mass or more and 0.23% by mass or less.
Citation Information
Patent Citations
Lead storage battery
JP2019067741A